2002
DOI: 10.1046/j.1365-2141.2002.03559.x
|View full text |Cite
|
Sign up to set email alerts
|

Manumycin inhibits farnesyltransferase and induces apoptosis of drug‐resistant interleukin 6‐producing myeloma cells

Abstract: Summary. Interleukin 6 (IL-6) is an important survival and growth factor for myeloma cells and exerts its effects by activating several transduction pathways, including the Ras cascade. As farnesylation of the activated Ras oncogene product by protein farnesyltransferase (FTase) is a critical step for Ras functional activity, FTase has emerged as a potential target for the development of new anti-cancer agents. Based on our previous demonstration that IL-6-producing myeloma cells are refractory to drug-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…Together, the data from this panel of experiments agree with those of Frassanito et al who showed that Man-A still induced apoptosis in IL-6-dependent multiple myeloma cells expressing both Bcl-2 and BclXL. 15 However, since ROS responses in the more resistant cells were only 25-30% of those noted in sensitive cells (Fig. 3a and data not shown), and because NAC prevented MEK and Akt processing and apoptosis in otherwise sensitive cells (Figs.…”
Section: Effect Of Protease Inhibitors On Signal Protein Processingmentioning
confidence: 81%
See 2 more Smart Citations
“…Together, the data from this panel of experiments agree with those of Frassanito et al who showed that Man-A still induced apoptosis in IL-6-dependent multiple myeloma cells expressing both Bcl-2 and BclXL. 15 However, since ROS responses in the more resistant cells were only 25-30% of those noted in sensitive cells (Fig. 3a and data not shown), and because NAC prevented MEK and Akt processing and apoptosis in otherwise sensitive cells (Figs.…”
Section: Effect Of Protease Inhibitors On Signal Protein Processingmentioning
confidence: 81%
“…10 Dysfunctional Ras is found in 30% of all known human cancers, including lymphomas and prostate cancers, 3 and moreover, constitutively active Ras is found in >90% of pancreatic cancers and in 20-30% of multiple myeloma isolates. 3,15 Therefore, compounds such as Man-A were especially prospected for their potential use as first lines of defense against tumors harboring constitutively active Ras. Because Ras controls pathways that regulate cell growth, catabolic processes, survival, proliferation and motility, 43 it is considered to be one of the most valued targets in anticancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the anti-neoplastic activity of Manu A has been demonstrated in various experimental systems (18). It exerts antitumor activity against a variety of cancer cells such as human pancreatic cancer cells (19), anaplastic thyroid cancer cells (20,21), human colon tumor cells (22) and human hepatocellular carcinoma HepG2 cells (23), medulloblastoma cells (24,25), leukemic cells (26), lymphoid tumor and myeloma cell lines (27,28). However, little is known concerning the anticancer mechanisms of Manu A by which it can induce apoptosis in MPM cells.…”
Section: Introductionmentioning
confidence: 99%
“…(Karp and Lancet, 2005;Santucci et al, 2003). Manumycin (Man)-A induces apoptosis in B-c e l l t u m o r s b y i n h i biting prenylation (Frassanito et al, 2002) and also by generating ROS that inhibits Ras/MEK/ERK and Ras/PI3K/Akt pathways by cleaving MEK and Akt (Sears et al, 2008). R115777 (zarnestra/tipifarnib) is a FTI that has shown promising clinical results in acute myeloid leukemia, myelodysplastic syndromes, chronic myelogenous leukemia, and MM and with anti-tumor effects noted independent of Ras mutations (Martinelli et al, 2008).…”
Section: Arsenic Trioxide (Ato)-preclinical Data Shows Ato Activity Imentioning
confidence: 99%